2013
DOI: 10.1016/j.desal.2012.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mass extractions and injections on the performance of a fixed-size humidification–dehumidification desalination system

Abstract: The impact of mass extractions and injections as a method for increasing the energetic performance of fixed-size humidification-dehumidification desalination systems is examined. Whereas previous studies of this problem have been restricted to thermodynamic models, the use of a more complete model that includes transport provides the ability to quantify the impact of mass extractions/injections on a realizable, fixed-size system. For a closed air, open water cycle, the results show that a single water extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…As is the case with most thermal desalination systems, effective recovery of the heat given off during condensation to provide part of the heat for further evaporation is the crux of maximizing the system's energy efficiency. Several works [11,[24][25][26][27] have explored ideas to equalize the effective capacity rates of the humidifier and dehumidifier so as to optimize heat recovery between the two components, including extracting a portion of the flow of the air or the water stream from one component and injecting it into the other. The particular difficulty in applying the theory of equipartition to an HDH system results from the thermodynamics of a saturated air-water mixture: temperature and humidity are not independent and are nonlinearly related.…”
Section: Humidification-dehumidificationmentioning
confidence: 99%
See 1 more Smart Citation
“…As is the case with most thermal desalination systems, effective recovery of the heat given off during condensation to provide part of the heat for further evaporation is the crux of maximizing the system's energy efficiency. Several works [11,[24][25][26][27] have explored ideas to equalize the effective capacity rates of the humidifier and dehumidifier so as to optimize heat recovery between the two components, including extracting a portion of the flow of the air or the water stream from one component and injecting it into the other. The particular difficulty in applying the theory of equipartition to an HDH system results from the thermodynamics of a saturated air-water mixture: temperature and humidity are not independent and are nonlinearly related.…”
Section: Humidification-dehumidificationmentioning
confidence: 99%
“…Several other works on HDH systems [24][25][26][27] have successfully applied the central idea behind equipartition-designing for a more uniform distribution of driving forces-but have compared systems with different boundary conditions such that the computation of equipartition factors for cases in these works may not provide a meaningful comparison (i.e., the systems may not have fixed average driving forces or fixed sizes, and thus may achieve performance gains from a combination of effects, only one of which is equipartition). Nevertheless, HDH is a significant example of real-world performance gains achieved [25] in part by application of the ideas behind equipartition.…”
Section: Humidification-dehumidificationmentioning
confidence: 99%
“…For example, the humidifier and dehumidifier may both be multistage bubble columns [46,47], which have much lower heat and mass transfer resistances [48] than packed beds or indirect contact heat exchangers. The extraction and injection of water or air from one component to the other in order to balance the humidifier or dehumidifier and increase energy efficiency has also been investigated [49][50][51][52][53]. For the purposes of this analysis, which is to show the effect of high salinity on energy consumption and efficiency, the thermodynamic investigation of the zero extraction cycle is sufficient; research on the high-salinity single-and multi-extraction variants is ongoing.…”
Section: Humidification-dehumidificationmentioning
confidence: 99%
“…Previous attempts to balance HDH systems with the water-heated, closed-air, open-water configuration reported some cases where it was more beneficial to extract air or water from the dehumidifier to the humidifier [25,26]. This odd finding was possible because the flow rates in the bottom stage were fixed at values that were very far from the optimum, and extracting in the wrong direction could actually make the system perform better.…”
Section: The Proper Direction Of Extractionmentioning
confidence: 90%
“…Thiel et al [26] used transport models of a packed-bed humidifier coupled with a tube-in-tube dehumidifier to study the effect of an extraction on the performance of a fixed-area system. They found that a water extraction from the dehumidifier to the humidifier could be beneficial with certain boundary conditions.…”
Section: Improvements To the Energy Efficiency Of Hdhmentioning
confidence: 99%